Superoxide Production by the Red Tide-Producing Chattonella marina Complex (Raphidophyceae) Correlates with Toxicity to Aquacultured Fishes - Tomoyuki Shikata; Koki Yuasa; Saho Kitatsuji; Setsuko Sakamoto; Kazuki Akita; Yuichiro Fujinami; Yoshitaka Nishiyama; Toshihisa Kotake; Ryusuke Tanaka; Yasuhiro Yamasaki (Antioxidants, 2021)
The marine raphidophyte Chattonella marina complex forms red tides, causing heavy mortalities of aquacultured fishes in temperate coastal waters worldwide. The mechanism for Chattonella fish mortality remains unresolved. Although several toxic chemicals have been proposed as responsible for fish mortality, the cause is still unclear. In this study, we performed toxicity bioassays with red sea bream and yellowtail. We also measured biological parameters potentially related to ichthyotoxicity, such as cell size, superoxide (O2•−) production, and compositions of fatty acids and sugars, in up to eight Chattonella strains to investigate possible correlations with toxicity. There were significant differences in moribundity rates of fish and in all biological parameters among strains. One strain displayed no ichthyotoxicity even at high cell densities. Strains were categorized into three groups based on cell length, but this classification did not significantly correlate with ichthyotoxicity. O2•− production differed by a factor of more than 13 between strains at the late exponential growth phase. O2•− production was significantly correlated with ichthyotoxicity. Differences in fatty acid and sugar contents were not related to ichthyotoxicity. Our study supports the hypothesis that superoxide can directly or indirectly play an important role in the Chattonella-related mortality of aquacultured fishes.